Analysis of JHS Students’ Attitudes toward Mathematics and Its Effect on the Academic Achievement: The Case of Asunafo South District - Poku, D.A. (University of Ghana, 2019)
The aim of the study was to assess the attitude of Junior High School students with regard to mathematics and its impact on their academic performance, a case of Asunafo South District. Thus, the study examined the relationship between attitude of students towards mathematics and their achievement in mathematics. The study investigated whether or not there is a connection between attitudes and learning experiences of JHS students in mathematics. Finally, it also examined differences between the gender and its impact on students’ mathematical performance. The study consisted of 360 students from 24 Junior High Schools in the Asunafo South District using the triangulation mixed method approach. The quantitative data from semi-structured questionnaires and their individual test scores were analyzed using descriptive and inferential statistics while the qualitative data from the interviews conducted were analyzed thematically. The results of the study showed that students have a positive attitude towards mathematics learning in the selected schools and that reflected in a strong positive correlation between attitude and mathematics performance in their field of study. The study demonstrated also that the students’ environment, in respect to the attitudes of mathematics teachers and their colleagues, has a greater impact on their math scores. The results again showed that there is no gender difference in respect to the study of mathematics and that both boys and girls performed same mathematically. The study recommends the development of positive attitude of students through motivational packages for performance and establishment of mathematical centres.
MPhil. Education
Keywords: Attitude; Achievement; Learning Environment; Asunafo South District